Rola rówieśniczego tutoringu w edukacji inkluzyjnej uczniów z niepełnosprawnościami - Twardowski, Andrzej (Studia Edukacyjne, 2018)
Researchers and teachers are interested in implementing best practices that improve inclusion of students with disabilities in ordinary schools. One solution to overcome these challenges is the implementation of peer tutoring as a flexible, peer-mediated strategy that involves students serving as academic tutors and tutees. In this article the author analyzes the following issues: 1) genesis and essence of inclusive education, 2) theoretical basis of peer tutoring, 3) peer tutoring in dyads, 4) peer tutoring in classroom, and 5) conditions for implementing peer tutoring.